2019
DOI: 10.1177/0269216319871666
|View full text |Cite
|
Sign up to set email alerts
|

Identification and evaluation of observational measures for the assessment and/or monitoring of level of consciousness in adult palliative care patients: A systematic review for I-CAN-CARE

Abstract: Background: The use of observational measures to assess palliative care patients’ level of consciousness may improve patient care and comfort. However, there is limited knowledge regarding the validity and reliability of these measures in palliative care settings. Aim: To identify and evaluate the psychometric performance of observational level of consciousness measures used in palliative care. Design: Systematic review; PROSPERO registration: CRD42017073080. Data sources: We searched six databases until Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 105 publications
(317 reference statements)
1
19
0
Order By: Relevance
“… 71 Existential distress has been linked to aspects such as loss of personal meaning and purpose to life, fear of death, despair, hopelessness, loss of dignity, sense of isolation. 72 , 73 No instruments were reported in the included articles. However, a review on available instruments to assess suffering for use in palliative care has identified instruments for assessing psycho-existential suffering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 71 Existential distress has been linked to aspects such as loss of personal meaning and purpose to life, fear of death, despair, hopelessness, loss of dignity, sense of isolation. 72 , 73 No instruments were reported in the included articles. However, a review on available instruments to assess suffering for use in palliative care has identified instruments for assessing psycho-existential suffering.…”
Section: Discussionmentioning
confidence: 99%
“… 39 The RASS-PAL has received the highest rating on psychometric properties together with the Consciousness Scale for Palliative Care, according to a recent systematic review evaluating instruments to monitor level of consciousness on palliative patients. 73 The other two instruments identified in the current review and validated for palliative care are the KNMG sedation score of the Royal Dutch Medical Association 62 and the Consciousness Scale for Palliative care. 8 The former being mainly used in Dutch contexts and the latter reported as easy to use.…”
Section: Discussionmentioning
confidence: 99%
“…22 Non-stimulating and non-invasive monitoring (including processed, electroencephalogram-based depth of sedation devices and nociception monitoring) could allow a more objective and frequent assessment of the levels of consciousness and analgesia during palliative sedation compared to clinical scales. 23,24 Depth of sedation monitoring tools such as the Bispectral Index (BIS), Entropy, and NeuroSense, have been used to monitor anesthesia and sedation, with the aims of decreasing the incidence of intraoperative awareness and reducing both anesthetic consumption and recovery time. [25][26][27] For this method, a disposable wet gel electrode is placed on the patient's forehead to record electric signals from the cortex and transfer them to a digital converter.…”
Section: Introductionmentioning
confidence: 99%
“…Non-stimulating and non-invasive monitoring (including processed, electroencephalogram-based depth of sedation devices and nociception monitoring) could allow a more objective and frequent assessment of the levels of consciousness and analgesia during palliative sedation compared to clinical scales. 23,24…”
Section: Introductionmentioning
confidence: 99%
“…To assess the level of comfort of these unconscious patients, usually subjective behavior-based observational scales are used. However, a number of studies have recently questioned the accuracy and validity of such scales in these situations [3]. Although several efforts have been made to improve these observational scales for the palliative patient group, the main problem with observational assessment methods for palliatively sedated patients is related to the medication itself.…”
Section: Introductionmentioning
confidence: 99%